2021
DOI: 10.33547/oda-sah.11.gog.11
|View full text |Cite
|
Sign up to set email alerts
|

Identyfikacja śladów użytkowania kamiennych i ceramicznych form odlewniczych z późnej epoki brązu / Identification of traces of use on Late Bronze Age stone and ceramic casting moulds

Abstract: A unique set of one- and two-piece casting moulds was found in a cremation burial (grave no. 24) discovered in a Late Bronze Age (900–800 BC) biritual cemetery of the Lusatian Culture in Gogolin-Strzebniów (Silesia), on the basis of which this grave was considered to be the burial of a bronze foundryman. Four two-piece moulds (two ceramic and two stone) and one ceramic one-piece mould were subjected to microscopic observations and spectral studies in order to identify potential traces of use, especially use in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The other, marked wi_11_3, was cast in a mold with a rectangular cross-section, showing visible casting defects on both top and bottom surfaces, indicating a high level of alloy outgassing. stone and clay one-piece molds for casting elongated ingots have been found in various regions, including Halle (saale) in saxony-anhalt and gogolin in Upper silesia, dating back to the late Bronze age (1300-800 BC) [31][32]. it is likely that such simple and reproducible shapes of raw material were also mass-produced using sand and metal molds.…”
Section: Research Results and Discussion Manufacturing Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The other, marked wi_11_3, was cast in a mold with a rectangular cross-section, showing visible casting defects on both top and bottom surfaces, indicating a high level of alloy outgassing. stone and clay one-piece molds for casting elongated ingots have been found in various regions, including Halle (saale) in saxony-anhalt and gogolin in Upper silesia, dating back to the late Bronze age (1300-800 BC) [31][32]. it is likely that such simple and reproducible shapes of raw material were also mass-produced using sand and metal molds.…”
Section: Research Results and Discussion Manufacturing Techniquementioning
confidence: 99%
“…central europe areas have yielded a considerable number of mass deposits (hoards) containing hundreds of such rings [10,[27][28]. it has been suggested that sickles may have played a similar role in the late bronze Age [29], but the primary form of raw material circulation during that time, as well as in the early Iron Age, would have been straight bar-shaped ingots [30][31][32]. The importance of ingots should be understood in the context of increasing population numbers, social complexity and the resulting demand for bronze products, which necessitated the diversification of production and the subsequent need for raw materials with different chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…W każdym obszarze przeprowadzono niezbędną dla rozpoznania składu chemicznego liczbę pomiarów. Zreferowane poniżej wyniki prac to kolejne działania badawcze przeprowadzone w ostatnich latach dla pradziejowych artefaktów wykonanych ze stopów miedzi (Garbacz-Klempka, Rzadkosz 2014;Garbacz-Klempka i in. 2015;2016;Garbacz-Klempka, Kwak, Kozana, Piękoś, Czekaj 2017;Garbacz-Klempka, Makarowicz, Tokarski 2017;Garbacz-Klempka, Suchy, Kwak, Długosz, Stolarczyk, 2018;Garbacz-Klempka, Suchy, Kwak, Tokarski, Klempka, Stolarczyk 2018).…”
Section: A N a L I Z A M E T A L O Z N A W C Z A I T E C H N O L O G ...unclassified
“…Siekierka została odlana w formie dwuczęściowej z rdzeniem. Formy do odlewania siekierek mogły być wykonane z kamienia lub wypalonej gliny (Gedl 1982;Malinowski 1982;Garbacz-Klempka et al 2016;Garbacz-Klempka, Dzięgielewski 2021). Znane są też trwałe, metalowe formy do odlewania siekierek (Machajewski, Maciejewski 2006;Sałat et al 2006;Baron et al 2014;Kłosińska, Sadowski 2017;Garbacz-Klempka 2018;Kowalski et al 2019a;2019b).…”
unclassified
“…Świadczy to o dużych trudnościach, jakie musiały występować w czasie zalewania form trwałych lub półtrwałych z rdzeniem przy odlewaniu siekierek z tulejką. Potwierdzają to również siekierki z wadami odlewniczymi, często znajdowane na stanowiskach archeologicznych (Garbacz-Klempka et al 2016;2018a). W przypadku siekierki z Falejówki wady w newralgicznych obszarach nie wystąpiły.…”
unclassified